2019
DOI: 10.2147/cia.s201615
|View full text |Cite
|
Sign up to set email alerts
|

<p>The value of screening for cognition, depression, and frailty in patients referred for TAVI</p>

Abstract: Background: Current surgical risk assessment tools fall short of appreciating geriatric risk factors including cognitive deficits, depressive, and frailty symptoms that may worsen outcomes post-transcatheter aortic valve implantation (TAVI). This study hypothesized that a screening tool, SMARTIE, would improve detection of these risks pre-TAVI, and thus be predictive of postoperative delirium (POD) and 30-day mortality post-TAVI. Design: Prospective observational cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…32 Khan et al included TAVI patients who were screened on the presence of geriatric risk factors. 33 They found that the presence of cognitive deficits (according to the Mini-Cog test) was associated with the occurrence of a postoperative delirium and 30-day mortality. 33 A possible explanation for this finding could be that patients with cognitive impairment are more prone to develop a postoperative delirium and that this is reflected in our outcome 'major postoperative complications during hospitalisation according to the Clavien-Dindo classification' and the composite outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Khan et al included TAVI patients who were screened on the presence of geriatric risk factors. 33 They found that the presence of cognitive deficits (according to the Mini-Cog test) was associated with the occurrence of a postoperative delirium and 30-day mortality. 33 A possible explanation for this finding could be that patients with cognitive impairment are more prone to develop a postoperative delirium and that this is reflected in our outcome 'major postoperative complications during hospitalisation according to the Clavien-Dindo classification' and the composite outcome.…”
Section: Discussionmentioning
confidence: 99%
“…33 They found that the presence of cognitive deficits (according to the Mini-Cog test) was associated with the occurrence of a postoperative delirium and 30-day mortality. 33 A possible explanation for this finding could be that patients with cognitive impairment are more prone to develop a postoperative delirium and that this is reflected in our outcome 'major postoperative complications during hospitalisation according to the Clavien-Dindo classification' and the composite outcome. However, only a minority (11.3%) of all patients with a Clavien-Dindo grade II complication experienced a delirium for which pharmacological treatment was necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Given that many CR centres intake thousands of new patients each year, a comprehensive single tool that assesses common neuropsychiatric comorbidities in CVD would be less time and resource consuming in a busy clinical setting such as CR, and would be more favourable for patient acceptability to undergo testing. In support of this, previous studies have shown that a composite screen was useful in identifying neuropsychiatric comorbidities and was predictive of long-term patient outcomes including impaired functioning and poorer community integration in patients post-stroke as well as post-operative delirium and mortality in patients post-transcatheter aortic valve implantation [2527]. Our goal was to develop a screening tool that would distinguish between CVD patients requiring referral (screen positive), those not requiring referral (screen negative) and those who need monitoring (intermediate), which could be administered in 10 min or less with minimal training.…”
Section: Introductionmentioning
confidence: 73%
“…In order to improve patient selection and to give patients a better basis for informed decisionmaking, identifying predictors of early mortality is important [6]. TAVI has shown to reduce mortality and improve both functional status and quality of life in older patients with aortic stenosis [7]. LogisticEuroSCORE (European System for Cardiac Operative Risk Evaluation)and the Society of Thoracic Surgeons Predicted Risk of Mortality (SRS-PROM) algorithm are the two most frequently used deathprediction models [8].…”
Section: Introductionmentioning
confidence: 99%